Portrayal of Dalit Women’s Struggles and Subjugation in Patriarchal (India) Society: A thematic Study - Mekathoti , Hemanthkumar (International Journal of Psychosocial Rehabilitation, 2020)
Taboo (Dalit) has existed in India for different epochs. Untouchability is an actual social ailment in Indian society. The thought of contamination, waste and tainting has led to Hindu society’s most noticeably awful underhandedness, called sacrosanct. Except for the revolutionary, the patriarchal and exploitation of regressive areas was a societal marvel of all human advances. Here, upper-caste men have seduced Dalit women and treated them like assistants and workers. Dalit women are the most egregiously poor victims of systemic failure to test long-standing evils. Someone knew them for their double segregation; they were victims of upper-caste men outside their homes and sexual fierceness within their homes, and poverty forced them to succumb to desire. Despite different innovations by social reformers in different periods of history, they altered social evils in India for all purposes.